2005
DOI: 10.1590/s0031-10492005000700001
|View full text |Cite
|
Sign up to set email alerts
|

Lista de tipos de Dermaptera e Orthoptera (Insecta) depositados no Museu de Zoologia da Universidade de São Paulo

Abstract: On this paper it is presented a list of the primary and secondary types of Dermaptera and Orthoptera housed at the Museu de Zoologia da Universidade de São Paulo. The collection includes types of 52 species from these two insect orders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…All participants were tested and re-tested after 10 min. Results indicated that after 10 min of MRT, the level of oxygenoglobin in the middle fibers of the trapezius increased (0.72 ± 1.47 vs. −0.14 ± 1.33 mmol/dL, p = 0.01) [40].…”
Section: Discussionmentioning
confidence: 90%
“…All participants were tested and re-tested after 10 min. Results indicated that after 10 min of MRT, the level of oxygenoglobin in the middle fibers of the trapezius increased (0.72 ± 1.47 vs. −0.14 ± 1.33 mmol/dL, p = 0.01) [40].…”
Section: Discussionmentioning
confidence: 90%